Identyfikacja preferencji z wykorzystaniem modeli PREFMAP - Zaborski, Artur (Identification of Preferences by PREFMAP Models, 2008)
The objective in PREFMAP analysis is to relate subjects' preferences to an existing configuration of the stimulus points. The article presents four hierarchical models of PREFMAP. These models are the four phases of the programme and each phase is a special case of the one preceding it. The subjects are mapped into the stimulus configuration as ideal points so that the preference scores are maximally reproduced in the distances from each subject points to the stimulus point.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 286-294